In-vitro antioxidant and in-vivo anti-aging with stress resistance on Caenorhabditis elegans of herbaceous peony stamen tea. Issue 1 (1st January 2021) - Meng, Jiasong; Cheng, Menglin; Liu, Lei; Sun, Jing; Condori-Apfata, Jorge Alberto; Zhao, Daqiu; Tao, Jun
ABSTRACT: Herbaceous peony ( Paeonia lactiflora Pall.) is a traditional Chinese medicinal herb with roots; however, the flowers, specifically the stamens have not been exploited. In this study, the main active components of P. lactiflora stamens (PLS) were identified, and in vitro antioxidant, in vivo anti-aging and stress resistance properties were examined using the nematode Caenorhabditis elegans . Our results showed that PLS contains 350 active components including flavonoids, phenolic acids, terpenoids, alkaloids, and others. PLS extracts at concentrations of 0.2–1.2 mg·mL −1 had strong antioxidant activity in vitro and showed a linear increase of concentration. The value of absorbance, scavenging activity of ·OH, DPPH and ABTS was 0.84, 31.55%, 84.67%, and 99.49% at 1.2 mg·mL −1, respectively. Moreover, PLS extracted at the same concentrations had no toxic effects on C. elegans, and the treatment with 1.2 mg·mL −1 PLS extract significantly extended C. elegans lifespan that was not at the expense of reducing its reproduction and Escherichia coli OP50 growth. Furthermore, the same treatment extract enhanced their locomotion behavior and decreased their intestinal autofluorescence during the aging process. Additionally, the stress resistance of C. elegans under both heat and oxidative stress conditions were significantly induced by 1.2 mg·mL −1 PLS extract treatment. Collectively, these results demonstrated that PLS extract exerted both in vitro antioxidant and in vivo anti-aging together with stress resistance properties, which could provide the theoretical basis for its production and popularization in China.